Wage labour in southeast Asia since 1840 : - Kaur, Amarjit (Palgrave Macmillan, 2004)
The Australian National University is preparing a multivolume economic history of Southeast Asia which will for the first time place the remarkable economic changes of the late twentieth century within a broader historical framework. This series is at once a work of pioneering scholarship, since nothing remotely comparable has previously been attempted, and a work of synthesis, since hitherto discrete literatures in several disciplines and on ten countries must be integrated. The series will include several volumes on the economic history of the principal countries of Southeast Asia over the past 150 or so years, and a larger number of volumes integrating the whole region in terms of major themes in economic history. Each volume will be accessible to students and specialists alike, aiming to make coherent a history which has been fragmented or ignored. The Economic History of Southeast Asia Project has been supported by the Research School of Pacific and Asian Studies of The Australian National University and by Henry Luce Foundation.